2018
DOI: 10.29333/ejhbe/87086
|View full text |Cite
|
Sign up to set email alerts
|

Improving Science Education in Nigeria: The Role of Key Stakeholders

Abstract: The general poor performance of students in national examinations in recent past have brought about doubts from relevant quarters as to the activities of stakeholders towards improving students' performance in Science and generally Science Education. Researchers have succinctly identified causes of poor performance among students and have acted in various capacities to remediate this occurrence. However, government, teachers and students have peculiar challenges for effective and successful improvement from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Another study carried out by Badmus and Omosewo shows that in recent years, students perform poorly generally in national examinations and most especially in science subjects (Biology, Chemistry and Physics) as presented on Table 1 (Badmus & Omosewo, 2018). To this end, little has been said on the potential impact of COVID-19 on the educational sector in Nigeria, especially its effects on the performance of senior secondary school students who will be sitting for the national examinations (West Africa Senior Secondary Certificate Examination as well as National Examination Council).…”
Section: Introductionmentioning
confidence: 99%
“…Another study carried out by Badmus and Omosewo shows that in recent years, students perform poorly generally in national examinations and most especially in science subjects (Biology, Chemistry and Physics) as presented on Table 1 (Badmus & Omosewo, 2018). To this end, little has been said on the potential impact of COVID-19 on the educational sector in Nigeria, especially its effects on the performance of senior secondary school students who will be sitting for the national examinations (West Africa Senior Secondary Certificate Examination as well as National Examination Council).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these under achievement scores from this examination body which does not support technological growth of a nation come as a result of gender issues and school location. According to Badmus and Omosewo [2] for any nation to grow in technology the students' achievement in science related subject like Chemistry must be at least 70%. The researcher further asserted that the reason why most nations in some Latin American and Africa continents are still under develop is as a result of below distinctions on academic achievement of secondary school Chemistry students in the external examinations like WAEC and NECO.…”
Section: Introductionmentioning
confidence: 99%
“…Obikezie et al [9] reported that students taught practical science using innovative teaching method in urban located schools may or may not achieved better than their rural counterpart taught using the same method in western world. Badmus and Omosewo [2] and Anderson and Wall [20] reported that science students in most located schools do well not minding their gender when taught with innovative teaching method like GLM. George et al [17] asserted that students taught general science in some urban located schools with innovative teaching method achieved better than their rural counterpart taught the same concept with the same innovative teaching method in Onitsha education zone.…”
Section: Introductionmentioning
confidence: 99%
“…Science education is very important to the development of any nation in many areas especially scientific and technological advancement (Sani & Ikpe, 2019). It comprises of three subjects namely biology, chemistry and physics; and if well-developed will represent a catalytic process for educational training, public awareness, values, behaviour and lifestyles required for a sustainable human and capital development (Badmus & Omosewo, 2018).…”
Section: Introductionmentioning
confidence: 99%